Libraries supporting online learning : a guide to facilitating access, community, and engagement - Mune, Christina D. (Santa Barbara, California, Libraries Unlimited, 2020)
"This how-to guide for librarians addresses all types of online learning, from hybrid courses to online PhD programs to MOOCs"--
Part I: Facilitating Access -- What Is Online Librarianship? -- Understand How You Help: Evaluating Your Services to Online Learners -- Help Them Find What They Need: Making Resources Discoverable, Sharable, and Affordable -- Part II: Creating Community -- Help Them Help Each Other: Facilitating Peer Interactions and Creating Online Learning Communities -- Help Them Connect with You: Deploying Effective Online Communication Tools -- Part III: Building Engagement -- Help Them Help Themselves: Information and Digital Literacy for the Online Learner -- Keep a Digital Toolbox: A Bibliography of Useful (and Mostly Free) Tools for Supporting Online Learning.
Includes bibliographical references and index.
Keywords: Libraries and distance education; Information literacy -- Web-based instruction; Web-based instruction -- Design; Libraries -- Special collections -- Electronic information resources; Libraries and community